Hydrogen peroxide modulates angiotensin II-induced contraction of mesenteric arteries from streptozotocin-induced diabetic rats - Chin, L.C.; Achike, F.I.; Mustafa, Mohd Rais (Elsevier, 2007)
Hydrogen peroxide (H2O2) contributes in the regulation of vascular tone, especially in pathological states. The role of H2O2 and superoxide anion free radicals in angiotensin II (Ang II)-induced contraction of diabetic tissues was examined with the aim of elucidating the underlying mechanisms.Isometric tension in response to various drug treatments was measured in isolated superior mesenteric arteries of streptozotocin (STZ)-induced diabetic WKY rats using the Mulvany wire myograph. Compared to the normal (euglycaemic) arteries, the Ang II-induced contraction was significantly reduced in diabetic arteries. Superoxide dismutase (SOD; converts superoxide to H2O2) significantly reduced the contraction in both types of arteries — an effect abolished by catalase (H2O2 scavenger), suggesting that the SOD effect was mediated by H2O2. Treatment with catalase had no effect on the Ang II contraction in euglycaemic arteries, but it raised the contraction in diabetic arteries to euglycaemic levels. This increase was similar to that observed with diabetic arteries incubated with L-NAME. Combined catalase and L-NAME treatment further enhanced the contraction in diabetic arteries, suggesting that the catalase effect was not mediated by nitric oxide (NO). The catalase effect was abolished by indomethacin treatment. These results suggest that attenuation of Ang II-induced contraction in diabetic tissues is modulated by endogenous H2O2, the scavenging of which unmasks an indomethacin-sensitive (and therefore cyclooxygenase product-mediated) Ang II-induced contraction.